2017
DOI: 10.1063/1.4990046
|View full text |Cite
|
Sign up to set email alerts
|

BaTiO3-based piezoelectrics: Fundamentals, current status, and perspectives

Abstract: We present a critical review that encompasses the fundamentals and state-of-the-art knowledge of barium titanate-based piezoelectrics. First, the essential crystallography, thermodynamic relations, and concepts necessary to understand piezoelectricity and ferroelectricity in barium titanate are discussed. Strategies to optimize piezoelectric properties through microstructure control and chemical modification are also introduced. Thereafter, we systematically review the synthesis, microstructure, and phase diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
559
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 943 publications
(617 citation statements)
references
References 437 publications
17
559
0
5
Order By: Relevance
“…This work outlines an approach to delineate different creep regimes and offers tools to investigate changes to the microstructure, which will be correlated with changes observed in electrical conductivity, dielectric, ferroelectric, and piezoelectric properties. For this first study, the prototype ferroelectric BaTiO 3 was chosen as the model material …”
Section: Introductionmentioning
confidence: 99%
“…This work outlines an approach to delineate different creep regimes and offers tools to investigate changes to the microstructure, which will be correlated with changes observed in electrical conductivity, dielectric, ferroelectric, and piezoelectric properties. For this first study, the prototype ferroelectric BaTiO 3 was chosen as the model material …”
Section: Introductionmentioning
confidence: 99%
“…Many experimental studies on the effect of grain size on properties have been reported in ferroelectric polycrystalline ceramics . These papers consistently report that the piezoelectric response drastically decreased for an average grain size <1 µm for typical ferroelectric materials (Pb(Zr,Ti)O 3 (PZT) or BaTiO 3 ).…”
Section: Introductionmentioning
confidence: 93%
“…Microstructure effects on piezoelectric response are one of the most important but complicated topics in polycrystalline ferroelectrics. The texture of polycrystalline ceramics directly affects the piezoelectric response and contributes to residual strains due to the thermal expansion anisotropy of the materials as well as the ferroelectric switching behavior . Among these microstructure parameters, grain size is an important parameter in determining the piezoelectric response.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 5A, the unipolar strain loops tend to become increasingly saturated with increasing external field due to a more complete ergodic relaxor-ferroelectric transformation at a high field. 41,42 As shown in Figure 5B and Figure S4B, the excellent strain performance of the BZT4 sample remains stable with variations of less than 2% in the frequency range of 1-20 Hz. However, BZT6 presents a lower strain response than BZT4 since the BZT6 composition deviates to a large extent from the ferroelectric (nonergodic)-relaxor (ergodic) phase boundary ( Figure 1I), which increases the actuating field required for triggering the reversible phase transition.…”
mentioning
confidence: 88%
“…34,35 Figure 5A-C presents the unipolar S-E curves at various electric fields, frequencies and temperatures, respectively, to further evaluate the practical potential of BZT4 in actuator applications. [2][3][4]9,[12][13][14][15][16][17]28,[36][37][38][39][40][41][42][43][44][45] It shows that most NBTbased incipient piezoceramics present a large strain hysteresis of 50%-80%, which is disadvantageous to practical applications. As shown in Figure 5A, the unipolar strain loops tend to become increasingly saturated with increasing external field due to a more complete ergodic relaxor-ferroelectric transformation at a high field.…”
mentioning
confidence: 99%